KONTRIBUSI KERAJINAN BAMBU DALAM MENINGKATKAN KESEJAHTERAAN PENGRAJIN BAMBU DI DUSUN TIMBE DESA LOYOK KECAMATAN SIKUR KABUPATEN LOMBOK TIMUR - mimi cahayani; Reza Pahlevi (Fakultas Ekonomi Universitas Islam Al-Azhar, 2018)
The study discusses the contibution of bamboo cafts in impromiving the welfare of craftsmen in Timbe Loyok village, Sikut district Lombok Timur. In the study analyzed the extent of the contribution of bamboo crafts in improving the welfarre of bamboo caftsmen. The purpose of this study was to determine the contibution of bamboo cafts to the level of income and welfae of bamboo craftsmen in the Timbe Loyok village siku district Lombok Timur. The purpose of this study was to the level of bamboo crafts to te level of income and te level of wwelfae oof craftsmen in timbe loyok villae sikur distict lombok timur. Te obect of tis study was in Timbe Loyok village Sikur Distrrict Lombok Timur. This research includes qualitive research. Analysis tekhniques used in esearch to collect data with obsevtion, intervew and documentation techniques. The esult of tis study indicate that bamboo handicrafts have a contribution in increasing the income and welfare of thhe crafsmen